Pengaruh Tindakan Alih Baring terhadap Nilai Saturasi Oksigen dan Heartrate Pasien Neonatus di Ruang Peristi RSI Sultan Agung Semarang - Nurisa Banowati; Indra Tri Astuti; Nopi Nur Khasanah (STIKes Ibnu Sina Ajibarang, 2025)
Monitoring hemodynamic conditions, particularly oxygen saturation (SpO₂) and heart rate, is a crucial aspect of neonatal care, especially in critical conditions. In addition to therapeutic interventions, supportive measures such as repositioning (postural change) can help optimize ventilation distribution and lung function, which directly affect hemodynamic stability. This study aimed to examine the effect of repositioning on oxygen saturation and heart rate levels in neonates in the Peristi Room at RSI Sultan Agung Semarang. This research employed a one-group pretest-posttest design with 27 neonatal respondents. The procedure involved alternating the neonates’ positions to supine, right lateral, and left lateral for two hours in each position, followed by measurement of SpO₂ and heart rate before and after repositioning. Data analysis was conducted using the Wilcoxon signed-rank test, as some data were not normally distributed. The results showed a significant difference in heart rate after the right lateral position (p=0.027), while the change in SpO₂ was not significant (p=0.125). The left lateral and supine positions showed no significant changes in either heart rate or SpO₂ (p>0.05). It can be concluded that repositioning, particularly in the right lateral position, positively influences hemodynamic stability in neonates. Future studies are recommended to include a larger sample size for more comprehensive findings.